HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN KESEHATAN JIWA REMAJA DI SMP NEGERI 4 TANIMAR SELATAN MALUKU - Ester Lontoh; Ariska Ariska; Maria Rangkoli (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Adolescence is a very important stage of life for mental health. The changes that occur include biological development, cognitive development, and psychological development. If teenagers cannot adapt to this, teenagers will experience stress. Social support is a source of well-being which is a protective factor against stress. The research objective is to determine the relationship between family social support and adolescent mental health at SMP Negeri 4 Tanimbar Selatan Maluku. This research is a descriptive analytical method using a cross sectional method. The research was carried out in January 2024 at SMP Negeri 4 Tanimbar Selatan Maluku. The population in this study was 112 respondents, the sample used a purposive sampling technique, namely 53 respondents. The population in this study was 35 respondents, the sample was 35 people. The statistical test used was the paried t-test with a significance level of 95% (α < 0.05). The results obtained by family social support for teenagers are mostly in the good category, namely 37 respondents (69.8%), the mental health of teenagers is mostly in the positive category, namely 33 respondents (62.3%), chi square statistical test results obtained a value of P = 0.001 or P < 0.05. The conclusion from the research results is that there is a relationship between family social support and adolescent mental health at SMP Negeri 4 Tanimar Selatan Maluku. Suggestions for schools to provide health education about mental health in early teens and provide counseling guidance rooms to become a forum for students to overcome problems that arise related to mental health conditions in their students.